Effect of pH on ionic liquid mediated synthesis of gold nanoparticle using elaiseguineensis (palm oil) kernel extract - Irfan, M. (Institute of Physics Publishing, 2017)
This study was conducted for microwave assisted synthesis of stable gold nanoparticles (AuNPs) by reduction of chloroauric acid with Elaeis Guineensis (palm oil) kernel (POK) extract which was prepared in aqueous solution of ionic liquid, EMIMOAc, 1-Ethyl-3-methylimidazolium acetate. Effect of initial pH of reaction mixture (3.5 - 8.5) was observed on SPR absorbance, maximum wavelength (λmax ) and size distribution of AuNPs. Change of pH of reaction mixture from acidic to basic region resulted in appearance of strong SPR absorption peaks and blue shifting of λmax from 533 nm to 522 nm. TEM analysis revealed the formation of predominantly spherical AuNPs with mean diameter of 8.51 nm. Presence of reducing moieties such as flavonoids, phenolic and carboxylic groups in POK extract was confirmed by FTIR analysis. Colloidal solution of AuNPs was remained stable at room temperature and insignificant difference in zeta value was recorded within experimental tenure of 4 months. © Published under licence by IOP Publishing Ltd.